2012
DOI: 10.2298/pac1201001s
|View full text |Cite
|
Sign up to set email alerts
|

Electron backscatter diffraction in materials characterization

Abstract: Electron Back-Scatter Diffraction (EBSD) is a powerful technique that captures electron diffraction patterns from crystals, constituents of material. Captured patterns can then be used to determine grain morphology, crystallographic orientation and chemistry of present phases, which provide complete characterization of microstructure and strong correlation to both properties and performance of materials. Key milestones related to technological developments of EBSD technique have been outlined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…Electron Back Scattered Diffraction (EBSD) is used to follow the evolution of grains (size, shape, orientation) and sub-grains as a function of creep strain. This method is now largely used for studying metallic alloys and technical ceramics (see for example [8,9]) but its application on UO 2 is relatively new: only a few papers are available (see, for example: [10][11][12][13]), none of them, to the best of our knowledge, deals with mechanically tested samples. Its potential in this research field will therefore also be discussed in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Electron Back Scattered Diffraction (EBSD) is used to follow the evolution of grains (size, shape, orientation) and sub-grains as a function of creep strain. This method is now largely used for studying metallic alloys and technical ceramics (see for example [8,9]) but its application on UO 2 is relatively new: only a few papers are available (see, for example: [10][11][12][13]), none of them, to the best of our knowledge, deals with mechanically tested samples. Its potential in this research field will therefore also be discussed in this work.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] Other sources of enhancement reside in image processing, phase identification methods, and data analysis. 18,50 Improvements in SEM discussed in the previous section, such as the introduction of FEGs, have contributed to a significant enhancement of EBSD's spatial resolution. The interaction volume during EBSD measurements depends on the material density and beam acceleration voltage, and the increasing sensitivity of detectors has made it possible to reach lower acceleration voltages.…”
Section: Ebsd Measurements and Interpretationmentioning
confidence: 99%
“…14 Furthermore, overviews of the application of EBSD in characterization of grain and subgrain structures, 15 applications in steels research, 16 and EBSD in conjunction with other characterization techniques are available. 17,18 In 2011, Zaefferer critically assessed EBSD and diffraction-based techniques in the transmission electron microscope (TEM), comparing them with respect to, e.g., their spatial and angular resolution. 19 He concluded that EBSD is in many cases preferred over the TEM techniques for orientation mapping, but for truly nano-crystalline materials, TEM was suggested to be superior.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction (XRD) and Electron backscatter diffraction (EBSD) are commonly used for texture analysis. EBSD method gives an accurate information about individual grains orientations and local texture [15]. However, XRD method has the advantage over EBSD of being able to provide information about crystallographic texture on a global statistical scale as the studied zones are larger and the penetration depth for XRD is more important [16].…”
Section: Introductionmentioning
confidence: 99%